2019
DOI: 10.21705/mcbs.v3i2.60
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant, α-Glucosidase Inhibitory Activity and Molecular Docking Study of Gallic Acid, Quercetin and Rutin: A Comparative Study

Abstract: Background: Plant-phenolics and flavonoids, including gallic acid, quercetin and rutin, are considered as safe inhibitors for α-glucosidase. This study aimed to compare antioxidant and α-glucosidase inhibitory activities of gallic acid (GA), quercetin (QUE) and rutin (RUT).Materials and Methods: Pure compounds of GA, QUE, and RUT were used. Their antioxidant and inhibitory activity on α-glucosidase were investigated spectroscopically, including their kinetic analysis and interaction mechanism by docking simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 0 publications
1
28
0
1
Order By: Relevance
“…It was shown that the docked conformation (pink line) and the crystal structure conformation (yellow line) of acarbose overlapped well, and the root mean square deviation (RMSD) of the overlap was 0.75 Å, which proved the reliability and reasonability of box parameter settings in docking ( Figure S2). Furthermore, many investigations confirmed that GA was shown to be a competitive inhibitor on α-glucosidase, similar to that found for acarbose, suggesting that GA and acarbose bound with α-glucosidase at similar binding sites in a manner that prevented substrate binding [32][33][34]. Based on the confirmed statements previously reported, we defined the box using the binding site of acarbose as a reference during docking.…”
Section: Molecular Dockingsupporting
confidence: 66%
“…It was shown that the docked conformation (pink line) and the crystal structure conformation (yellow line) of acarbose overlapped well, and the root mean square deviation (RMSD) of the overlap was 0.75 Å, which proved the reliability and reasonability of box parameter settings in docking ( Figure S2). Furthermore, many investigations confirmed that GA was shown to be a competitive inhibitor on α-glucosidase, similar to that found for acarbose, suggesting that GA and acarbose bound with α-glucosidase at similar binding sites in a manner that prevented substrate binding [32][33][34]. Based on the confirmed statements previously reported, we defined the box using the binding site of acarbose as a reference during docking.…”
Section: Molecular Dockingsupporting
confidence: 66%
“…Because the cavity of the site is large enough to accommodate polysaccharides, the authors supposed that sm molecules cannot bind as well in the active site as larger molecules, as rutin, being than quercetin, could demonstrate [46]. These two cases also revealed that querceti different inhibitory modes with a noncompetitive inhibition of α-amylase vs a compe inhibition of α-glucosidase [10,46]. The results showed effective inhibition of intestinal α-glucosidase by both (−)-catechin and gallic acid, whereas thymoquinone was not active under the evaluated concentration range (data not shown).…”
Section: Mechanism and Ic 50 Determinationsmentioning
confidence: 99%
“…reptans leaves on α-glucosidase. Various phenolic and flavonoid compounds have been reported to inhibit αglucosidase in vitro (Limanto et al, 2019;Yin et al, 2014).…”
Section: In Vitro Antidiabetic Activitymentioning
confidence: 99%